DYNAMICS OF INFESTATION OF CALVES WITH THE MAJOR NEMATODE SPECIES IN CONDI-TIONS OF THE NORTHEASTERN CAUCASUS - Z. T. Bajsarova; S. T. Ajshanov (Российский паразитологический журнал, 2016)
Objective of research: to study the infestation period of calves with the major nematode species in conditions of the Chechen Republic. As a research object served the calves from birth to one year of age. Materials and methods: 69 calves from birth to one year of age were gazing in pastures of Shelkovsk region of Chechnya where cattle previously had been kept spontaneously infected with Strongylata of gastrointestinal tract and lungs. Fecal samples of calves were taken monthly and examined after the preliminary cultivation of infected larvae. The infestation period of calves was determined at the beginning of release of eggs and larvae with feces. The species belonging of trematode larvae was identified according to larva morphology and number of intestinal cells. Results and discussion: It is determined that for the first time the eggs/larvae of trematodes Ostertagia, Cooperia, Trichostrongylus and Dictyocaulus have been found in feces in June, and the eggs/larvae of Haemonchus and Oesophagostomum – in July. In the next months the invasion of calves has increased. The first cases of Strongylata infection in calves are reported in May. The massive infestation of calves occurs by the end of the summer. The highest level of Dictyocaulus viviparus infection is reported in July-August, with Nematodirus spp., Ostertagia sp., Trichostrongylus sp. – in August-September, Cooperia sp., Haemonchus sp. и Oesophagostomum sp. – In September-October. The calf infestation in May is supposedly caused by the presence of the infected overwintered larval nematodes. The maximum infestation of calves at the end of summer and at the beginning of autumn serves as evidence that the infestation occurs most often during the summer period.